An Analysis of Language Styles Used in Fly-Tipping Spots in Banda Aceh and Aceh Besar - Putra Phoenna; Siti Sarah Fitriani; Masrizal Mahmud (Research in English and Education Journal, 2021)
Language style is the choice of words used by the speaker when speaking in different circumstances. Fly-tipping is an illegal dump of waste by people in certain area. The purpose of this study is to find out the types of language style used in fly-tipping spots in Banda Aceh and Aceh Besar. The source of data is warning boards and signs in 50 fly-tipping spots in Banda Aceh and Aceh Besar. The research design used is descriptive-qualitative research with content analysis approach. The instrument that is used to collect the data in this research is observation sheet. The data were analyzed and classified based on the types of language style proposed by Joos (1976) as cited in Hamdany and Damanhuri (2017). In analyzing the data, the researcher uses the data analysis method proposed by Miles et al. (2014) that the data are analyzed through three steps, those are data reduction, data display, and conclusion drawing. The results of this study show that from 50 data that are analyzed, the researcher only found three types of language style that are used. Those are formal style with 21 occurrences, consultative style with 22 occurrences, and casual style with only 7 occurrences. However, the researcher did not find any use of frozen style and intimate style from the analysis. This shows that people are more likely to use a clear, formal, and neutral language such as formal and consultative style to express something to the public, especially at the fly-tipping spots in Banda Aceh and Aceh Besar.